Potenciales Evocados Somatosensitivos obtenidos por estimulación del nervio Tibial (registros espinal y craneano) en caninos - Pellegrino, F.C. (2005)
We investigated SSEPs in 22 normal dogs of both sexes (12 females), aged between 3 and 14 years (mean: 7 +/- 4 years old) by recording the electrical signal at the spinal cord (L7-S1 and L5-L6) and at the scalp (frontoparietal region) in response to tibial nerve stimulation. Conduction velocity (CV) of tibial nerve and its roots was calculated, measuring the distance between the stimulating cathode and the recording electrode, and dividing it into the latency of the of the spinal cord arrival corresponding negative peak. Central conduction time (CCT) was estimated subtracting the latencies of the spinal potencial from the cranial potential. We employed needle electrodes sited between L7-S1 and L5-L6, and in the scalp. At the lumbosacral spinal level (L7-S1) 3 succesive potentials were obtained: the first is a triphasic wave; its first deflection being positive (P1-N1-P2) followed by a larger biphasic potential negative-positive (N2-P3) and ending down with another small biphasic wave negative- positive (N3-P4). The mean latency to the main negative peak (N2) was 6.21 ms +/-1.44 ms. The mean value for CV of tibial nerve was 59.03 +/-8.56 m/s. At the L5-L6 spinal level a triphasic wave was obtained, its first deflection being positive followed by a larger negative potential, ending with another small positive deflection. Cranial SSEPs had a "w" shape, their mean latency to the negative peak was 20.46 +/-3.15 ms. The mean value for CCT was 12.06 +/-2.28 ms. In regards to the sources of the L7-S1 potential, they may be attributed to the activity of the neurons located at the ganglia of the dorsal roots, the spinal roots, and the dorsal horn of the spinal cord, while L5-L6 potential may be due to the spatial summation activity of the different structures in the recording site. The cranial response is brought about by the activation of the thalamo-cortical circuits and the neurons of the parietal cortex situated at the receiving area.